1997
DOI: 10.1080/00288306.1997.9514763
|View full text |Cite
|
Sign up to set email alerts
|

Change in direction of the Pelorus River, Marlborough, New Zealand: Evidence from composition of Quaternary gravels

Abstract: Clasts in greenish subsurface gravels of presumed Quaternary age in the Kaituna valley comprise mainly metamorphosed and variably foliated volcanic litharenite of the Pelorus Group, but also contain some Dun Mountain Ophiolite Belt lithologies. These clast compositions are inconsistent with the gravel source being either the surrounding schist basement or the nearby Wairau River, but instead strongly suggest a source in the Pelorus River catchment. Thus, at some time in the Quaternary, the Pelorus River flowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As we have suggested, New Zealand’s active geological history provides considerable scope for formulating and testing evolutionary hypotheses. Here we have demonstrated a strong phylogeographical affinity between freshwater fish populations that were connected until the late Pleistocene (Mortimer & Wopereis, 1997) but subsequently diverged following drainage reversal. Specifically, G. divergens haplotypes from the Pelorus–Kaituna system represented the sister group to those from the Wairau River system, despite the fact that the former system drains north into the Marlborough Sounds, while the latter drains east into Cook Strait.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As we have suggested, New Zealand’s active geological history provides considerable scope for formulating and testing evolutionary hypotheses. Here we have demonstrated a strong phylogeographical affinity between freshwater fish populations that were connected until the late Pleistocene (Mortimer & Wopereis, 1997) but subsequently diverged following drainage reversal. Specifically, G. divergens haplotypes from the Pelorus–Kaituna system represented the sister group to those from the Wairau River system, despite the fact that the former system drains north into the Marlborough Sounds, while the latter drains east into Cook Strait.…”
Section: Discussionmentioning
confidence: 91%
“…The hypothesis of a historical drainage reversal specifically for the Pelorus–Kaituna system was tested and confirmed by Mortimer & Wopereis (1997), who identified Pelorus‐derived fossil gravels from the Wairau system. These authors tentatively suggested that the drainage reversal occurred 12 000–70 000 years ago, but more recent mapping of river terraces indicates an older date (128 000–186 000 years ago; D. Craw & J.M.…”
Section: Introductionmentioning
confidence: 91%
“…Our position on the Pacific and Indo-Australian tectonic plate boundary has led to extensive faulting and uplift. Through rapid uplift, erosion, and wholesale tilting of surfaces (individually or in combination), one river catchment can 'capture' the headwater of another (Bishop 1995;Mortimer & Wopereis 1997;Craw et al 2003Craw et al , 2008. Such geological scenarios can be tested by asking whether species distributions match ancient or current connections (Mayden 1988).…”
Section: Allopatric Speciation By Vicariant Geological Processes?mentioning
confidence: 99%